Alginate from Sargassum sp. Improve the Hematology Performance and Oxygen Tolerance Exposure of Lates calcarifer - Ervia Yudiati; Ali Djunaedi; Nuril Azhar; Rabia O. Alghazeer (Universitas Diponegoro, 2022)
Indonesia's fish production is abundant, especially in aquaculture. Lates calcarifer is farmed fish species. The failure of L. calcarifer cultivation due to disease problems. We are utilizing a natural compound derived from tropical Sargassum sp. extracts, namely alginate. This study aims to determine and analyse the supplementation of alginate in the diet by oral administration to improve the fish's hematological performance and oxygen stress tolerance. There were one control and three treatments (2 g.kg-1, 4 g.kg-1, and 8 g.kg-1 alginate/feed). The experiment was a completely randomized design with three replications. Fish were reared in a 350 L fiber tank for 12 days at a density of 20 ind.tank-1. Stress oxygen tolerance was applied by rearing the 10 fish in 12 L fully plastic-wrapped containers. The parameters test analyzed were phagocytic activity and phagocytic index, red blood parameters which are hematocrit and hemoglobin. The survival rate after 5 hr anoxic exposure was also recorded. The best treatments were achieved at a dose of 6 g.kg-1 and 8 g.kg-1in all parameters, except the phagocytic index. The alginate addition at all oxygen stress treatments also performed a better survival rate compared to the control. Adding alginate to feed as feed supplementation by oral administration can boost hematological performance and higher tolerance from oxygen stress exposure.